THE CONCEPT OF WORLDWIDE EDUCATION IN THE REVIEW OF ISLAMIC EDUCATION - Nurhikmah B; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2021)
The goal of this research was to determine the concept of global education in the review of Islamic education. This study is a descriptive qualitative study. Through the use of a phenomenological approach. Data collection methods rely on data sources such as semester learning plans, syllabi, observation, and interviews. Questionnaire has been completed. Documentation is required. The Miles and Huberman model data analysis technique was employed. Based on the study's findings, it is possible to conclude that in the application of VOSviewer. The research discovered that learning and cooperation are also formed in group activities in order to foster a positive attitude toward students in the classroom.The find of the research is learning and cooperation is also formed in group activities so as to be able to foster a positive attitude towards students in the worldwide education in the review of Islamic Educations